Mechanisms controlling bacterial infection in myeloid cells under hypoxic conditions - Hayek, Inaya; Schatz, Valentin; Bogdan, Christian; Jantsch, Jonathan; Lührmann, Anja (Cellular and Molecular Life Sciences, 2020)
Various factors of the tissue microenvironment such as the oxygen concentration influence the host–pathogen interaction. During the past decade, hypoxia-driven signaling via hypoxia-inducible factors (HIF) has emerged as an important factor that affects both the pathogen and the host. In this chapter, we will review the current knowledge of this complex interplay, with a particular emphasis given to the impact of hypoxia and HIF on the inflammatory and antimicrobial activity of myeloid cells, the bacterial responses to hypoxia and the containment of bacterial infections under oxygen-limited conditions. We will also summarize how low oxygen concentrations influence the metabolism of neutrophils, macrophages and dendritic cells. Finally, we will discuss the consequences of hypoxia and HIFα activation for the invading pathogen, with a focus on Pseudomonas aeruginosa, Mycobacterium tuberculosis, Coxiella burnetii, Salmonella enterica and Staphylococcus aureus. This includes a description of the mechanisms and microbial factors, which the pathogens use to sense and react to hypoxic conditions.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Bacteria; Dendritic cells; HIF1α; Hypoxia; Infection; Macrophages; Metabolism; Neutrophils